Fernando Collor na imprensa brasileira : representações em torno da sedução e da satanização - Souza, Paulo Roberto da Silva de (2008)
It approaches the representation of Fernando Afonso Collor de Mello in the main large circulation, widespread and nationally reverberating periodicals (magazines and newspapers) within the period between January of 1987 and December of 1992. It aims at raising considerations on the diversity of personal and professional relations and interests that marked Fernando Collor de Mello’s ascent in the national political scenario, allowing him to be a protagonist in the presidential election of 1989 , taking him away from presidency on December 29, 1992, and putting him in an eight-year quarantine. This study aims at unveiling the way these events happened during this short period of time, and which playing forces enabled his glorious entrance on the scene and made him be thrown away so dramatically. This study understands his representation in the press as a published version of facts. In the elaboration of this study, we used part of the literature produced by journalists who experienced this historical period and made comments both on the relation between the press and the candidates and on the election itself. This study also refers to editions of the weekly magazines Veja and IstoÉ-Senhor